Fusidic Acid Susceptibility in Staphylococci from Clinical Isolates at a Tertiary care Hospital in Lahore - Hussain, Sheraz (International Journal of Pathology, 2022)
Background: Staphylococcus is a genus of Gram-positive bacteria in the family Staphylococcaceae. Bacteria in the genus staphylococcus are pathogens of men and other mammals. Under the microscope they appear in clusters (like a bunch of grapes). Phenotypically the clinical important species are classified into two groups on the basis of coagulase enzyme production (i.e. their ability to clot blood plasma). These gram positive cocci are responsible for severe morbidity and mortality as they cause community and hospital acquired infections. Objective: To describe the susceptibility pattern among clinical isolates of Staphylococcus spp. using antimicrobial susceptibility test (disk diffusion method) to Fusidic acid. Material & Methods: This was a cross-sectional study conducted at Shalamar Teaching Hospital. A total of 120 Staphylococci spp. were isolated from different clinical specimens collected over a 3 month period in the microbiology laboratory. Specimens were inoculated by standard techniques on to blood agar. Identification was done by colonial morphology, Gram staining and conventional biochemical testing. Antimicrobial susceptibility test was performed on these isolates. Fusidic acid resistance was measured by zone of inhibition around the antibiotic containing disk. Result: Out of the 120 isolates, 38 were coagulase positive Staphylococci, 79% of which were sensitive to Fusidic acid and about 20 % resistant. Coagulase negative Staphylococci were 82 and out of these 45% were sensitive and 55% resistant to Fusidic acid. Conclusion: There is an increasing resistance noticed against coagulase negative Staphylococci to Fusidic acid while resistance in coagulase positive Staphylococci is only 20% and comparable with previous studies.